If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 40 = 5x + 13 Reorder the terms: 40 + 2x = 5x + 13 Reorder the terms: 40 + 2x = 13 + 5x Solving 40 + 2x = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 40 + 2x + -5x = 13 + 5x + -5x Combine like terms: 2x + -5x = -3x 40 + -3x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 40 + -3x = 13 + 0 40 + -3x = 13 Add '-40' to each side of the equation. 40 + -40 + -3x = 13 + -40 Combine like terms: 40 + -40 = 0 0 + -3x = 13 + -40 -3x = 13 + -40 Combine like terms: 13 + -40 = -27 -3x = -27 Divide each side by '-3'. x = 9 Simplifying x = 9
| -7x^2-6x=0 | | 375=3+(2)*561+-2r | | -(7y+3)-(-6y-8)=1 | | 7(p-6)= | | 5x+4=10x+10 | | 3x^2+23x+30=0 | | 2p+8p=10 | | -5=x-3 | | y=8x+27 | | an=-11+7n | | 3x^2+11x+28=0 | | 5x-6=3x+10 | | 3x-2=2x+5 | | r=3+(2)561+-2r | | x^2-4x-8=0 | | a+6=16 | | -12x-20y=60 | | 3x+4=7-2x | | b^2=15-2b | | 2x+6y=-24 | | 17.50b+35r=9817.50 | | f(4)=4x | | -7x-3y=42 | | f(4)=2x | | r=3+2b | | 9+7b=8b-7 | | 3(5y+6)-15y=18 | | 6x(2x-1)-7x=5x-1 | | 2(x+5)-8=92 | | -x+3y=27 | | 7x+12=4x+30 | | 5x+28(x-2)=241 |